2018
DOI: 10.3892/ijo.2018.4451
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA 00152 functions as a competing endogenous RNA to regulate NRP1 expression by sponging with miRNA‑206 in colorectal cancer

Abstract: Colorectal cancer (CRC) is the third most common type of cancer; however, the molecular mechanisms underlying colorectal tumor metastasis and growth remain elusive. Recently, accumulating evidence has indicated that long non‑coding RNAs (lncRNAs) play a critical role in CRC progression and metastasis; however, the biological role and clinical significance of lncRNA 00152 (lnc00152) in CRC remains largely unknown. Thus, in this study, lnc00152 expression was measured in 80 human CRC tissue samples, 40 non‑cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…LINC00152 is an 828 bp lncRNA located on chromosome 2p11.2. Previous studies have found that LINC00152 plays an oncogenic role in the development of a wide range of tumor types (Chen et al, 2018a; Chen et al, 2018c). Enhanced LINC00152 expression has also been found to be a potential prognostic biomarker in patients with lung and colorectal cancers (Chen et al, 2018b; Li et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00152 is an 828 bp lncRNA located on chromosome 2p11.2. Previous studies have found that LINC00152 plays an oncogenic role in the development of a wide range of tumor types (Chen et al, 2018a; Chen et al, 2018c). Enhanced LINC00152 expression has also been found to be a potential prognostic biomarker in patients with lung and colorectal cancers (Chen et al, 2018b; Li et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA PVT1 enhances the viability and invasion of papillary thyroid carcinoma cells by functioning as ceRNA of microRNA-30a to mediate the expression of insulin like growth factor 1 receptor [29]. LncRNA 00152 functions as a ceRNA to regulate NRP1 expression by sponging miRNA-206 in colorectal cancer [30]. Through bioinformatics tools and (See figure on previous page.)…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they play a major role in all stages of tumorigenesis and metastasis by [263]. In colorectal cancer, miR-206 inhibits tumor growth and invasion by downregulating the long non-coding RNA lnc00152 which again promotes NRP1 expression and EMT [264]. In addition, miRs can also mutually regulate their activity.…”
Section: Signaling and (Patho) Physiological Functions Of Nrpmentioning
confidence: 99%